Outcomes of pre-fermentation and post-fermentation extended maceration for anthocyanin and tannin composition of red wines from hot irrigated vineyards of south eastern Australia - Ioannidou, Danai (2012)
Mestrado Vinifera EuroMaster - Instituto Superior de Agronomia